Penyidikan tindak pidana pemilu dalam masa kampanye pada pemilihan anggota dewan perwakilan rakyat daerah studi kasus di Kabupaten Purworejo - Eka Wahyu Adi Saputra; Lilik Mulyadi; Eko Nurharyanto (Universitas Janabadra, 2020)
Election criminal acts are closely related when entering the current political year, general election crimes are all criminal acts related to the holding of general elections both regulated in and outside the electoral law. This study aims to determine the investigation as well as the obstacles in investigating election criminal acts using official cars in Purworejo Regency. This research uses normative research with descriptive research methods. The approach used is the statute approach and case approach. This research was conducted at Purworejo District Police, Purworejo Regency KPU, and Purworejo Regency Bawaslu. The type of data used is primary and secondary data. Primary data sources from interviews and observations, secondary data sources from primary legal materials and secondary legal materials. The data analysis technique used is qualitative descriptive analysis. The results of research on election crime cases deliberately violated the prohibition of the implementation of the election campaign by using government facilities in the form of official cars by the suspect Endang Tavip Handayani, SH binti Suparno based on Purworejo District Court Decree No: 31 Pid.Sus. 2019 PN Pwr, impose a sentence on the Defendant for 1 (one) month and a fine of ten million rupiah provided that if the fine is not paid, it is replaced with imprisonment for 15 days with a trial period of 3 (three months. Based on the decision of the Central Java High Court No: 134 Pid.Sus 2019 PT SMG sentenced the defendant to imprisonment for 1 month and a fine of Rp five million rupiah with the provisions if the fine Unpaid is replaced by imprisonment for 15 days. KPU Decision No: 1040 HK.03.1Kpt 3306 Kab V 2019 states removing the candidate from the permanent candidate list.